Vascular Endothelial Growth Factor Concentration in Brain of Rat Treated with Anaerobic Exercises - Rostika Flora; Muhammad Zulkarnain; Yuliana Ardi; Esti Sorena; Roslina Wati; Syokuma Wena; Rahmad Aswin Juliansyah; Samwilson Slamet (Intelektual Pustaka Media Utama, 2015)
Anaerobic exercise is a high-intensity exercise that needs quick energy supplies obtained in a very short time. However, this exercise may result in tissue hypoxia which is characterized by the increase of HIF-1α concentration. The presence of HIF-1α will induce the secretion of VEGF and, eventually, trigger angiogenesis. Nevertheless, it is still unclear whether anaerobic exercise will also cause hypoxia in which this condition will increase the concentration of VEGF in brain tissues. The aim of this study was to find out the effect of anaerobic exercise frequency towards VEGF concentration of Wistar rat brain tissues. Brain tissues were taken from rats treated with anaerobic exercise using treadmill. This exercise was given in different frequencies; one time, three times, and seven times a week. The data collected were analyzed using independent t-test. The results of this study showed that anaerobic exercise done once a week could significantly increase VEGF concentration (p < 0.05) if compared with the one in control group (95.21 ± 31.99 v.s. 63.36 ± 11.01 pg/mL). Meanwhile, VEGF concentration of treatment groups given exercise three times a week (47.97 ± 10.68 pg/mL) and seven times a week (40.56 ± 13.98 pg/mL) showed a significant decrease if compared with that of control group (63.36 ± 11.01 pg/mL). Anaerobic exercise affected VEGF concentration as an indicator of angiogenesis in brain tissue of wistar rats.